The Learning Outcomes of Physical Education Students According to Thai Qualifications Framework for Higher Education, Chiang Mai University - kaiket, chinawat; Rodwattanaditsakul, Natchajarn; Tuisry, Parkorn; Yantaragorn, Patara; Pukamarn, Thachakorn (Trends of Humanities and Social Sciences Research, 2021)
This research aimed to investigate and compare the opinion toward the learning outcomes according to the National Qualifications Framework for Higher Education. The sample consisted of 106 preservice teachers with the major of physical education in the Faculty of Education, Chiang Mai University in 2019. They were at different years of the program. The data was collected by using a self-reporting from the five-scale questionnaire with six aspects totaling accounted for 141 questions. Which was verified for content validity from each IOC by three experts, ranging from 0.67 to 1.00 and also calculated confidentially by using Cronbach’s alpha coefficient (a) that equal to 0.993. The data were analyzed to calculate frequency, percentage, mean, standard deviation and one-way analysis of variance, as well as Scheffé method. The results indicate that: The opinion toward the learning outcomes according to the National Qualifications Framework for Higher Education and individually regarding each aspect are collectively high. The highest mean is the moral and ethical aspect, following by the aspects of knowledge, the cognitive skills, interpersonal skills and responsibility, computational, communication and ICT skills, and learning skills. The opinion from the preservice teachers with different years were significantly different according to learners toward the National Qualifications Framework for Higher Education in the aspects of interpersonal skills and responsibility has a different in learning skills at the level of .05. However, Scheffé test indicated that there were no significant differences between each pair of the preservice teachers toward the different years.